Incomplete contract in private finance initiative (PFI)contracts: causes, implications and strategies - Mansor, Nur Syaimasyaza; Abdul Rashid, Khairuddin (2015)
An incomplete contract is a contract that fails to state all the parties’ rights and obligations, has gaps, missing provisions, and ambiguities in its terms and conditions. In theory, complete contracts cannot be achieved, and many contracts inevitably remained incomplete. This also applies to Private Finance Initiative (PFI) contracts. Human factors play an important role in determining the completeness of a contract. In the context of PFI contracts, this paper presents a critical review of incomplete contract, its causes, implications, and strategies.